Vernacular culture, city, architecture: analysis and correlation of concepts - Y. O. Butsykina, (Ukrainian Cultural Studies, 2021)
The article is devoted to structuring the existing definitions of three key concepts within modern vernacular cultural studies in order to build a holistic picture of understanding the vernacular elements in urban space. Within the definition of vernacular culture (M. Lantis, A. Markusen, J. Carr and L. Servon), characteristics such as the combination of traditional culture and modern aspects of cultural identity in the non-professional dimension of city life were identified. Within the definition of the concept of vernacular city (J. Krase and T. Shortell, S. Sapu and others) the appeal to the discourse of everyday (G. Simmel, H. Lefebvre, M. de Certeau, R. Sennett and M. Blonsky) and the method of visual semiotics (R. Jakobson) is analyzed in order to distinguish signs of visual representation and urban identity, social and cultural conditions in the construction of urban space by its inhabitants. The concept of vernacular architecture (R. Brown and D. Maudlin, H. Guillaud, M. Salman) carries a combination of elements of traditional and everyday within postmodern and postcolonial studies and the concept of "collage city", as well as through the prism of the problem of sustainability.
Keywords: vernacular architecture, vernacular culture, vernacular city, urban landscape, sustainability